2015
DOI: 10.1093/jxb/erv239
|View full text |Cite
|
Sign up to set email alerts
|

Root phenotyping: from component trait in the lab to breeding: Table 1.

Abstract: In the last decade cheaper and faster sequencing methods have resulted in an enormous increase in genomic data. High throughput genotyping, genotyping by sequencing and genomic breeding are becoming a standard in plant breeding. As a result, the collection of phenotypic data is increasingly becoming a limiting factor in plant breeding. Genetic studies on root traits are being hampered by the complexity of these traits and the inaccessibility of the rhizosphere. With an increasing interest in phenotyping, breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
158
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 160 publications
0
158
0
1
Order By: Relevance
“…In the last decade a wide range of new and improved methods to research roots in a more natural environment have been developed (as reviewed in Zhu et al, 2011; Downie et al, 2015; Judd et al, 2015; Kuijken et al, 2015). Most systems are based on either a transparent growth medium or a medium from which the roots can easily be removed without damage.…”
Section: Crop Selection On Rsa: the Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade a wide range of new and improved methods to research roots in a more natural environment have been developed (as reviewed in Zhu et al, 2011; Downie et al, 2015; Judd et al, 2015; Kuijken et al, 2015). Most systems are based on either a transparent growth medium or a medium from which the roots can easily be removed without damage.…”
Section: Crop Selection On Rsa: the Challengesmentioning
confidence: 99%
“…A wide range of root image analysis software exists (as reviewed in Lobet et al, 2013; Spalding and Miller, 2013; Kuijken et al, 2015). These tools range from automated to non-automated.…”
Section: Crop Selection On Rsa: the Challengesmentioning
confidence: 99%
“…The root system is by nature hidden, and root phenotyping platforms have to make a compromise between the relevance of growth conditions and trait measurement feasibility. Most root phenotyping platforms focus on measurements at high throughput of selected root traits on a large number of plants, with the objective of detecting quantitative trait loci usable in breeding (Kuijken et al, 2015). For example, Atkinson et al (2015) reported a phenotyping platform where root systems grow in 2D on a filter paper for a few days.…”
mentioning
confidence: 99%
“…In addition, root measurements tend to be more precise and more reproducible because the plants are grown in a more homogeneous environment compared to the field. Despite many innovations in root phenotyping over the last few years (Paez-Garcia et al, 2015;Kuijken et al, 2015), suitable methods for large breeding populations are still needed.…”
Section: Rhizoslidesmentioning
confidence: 99%
“…In the recent years, methods for phenotyping root traits have been developed in controlled environment conditions and in the field (Paez-Garcia et al, 2015;Kuijken et al, 2015).…”
Section: Introductionmentioning
confidence: 99%